1971
DOI: 10.1055/s-0028-1094132
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescent Identification of Cells Synthesizing Human Growth Hormone in Culture

Abstract: Hellerström, c.: A method for the microdissection of intact pancreatic islets of mammals. Acta endocr. (Kbh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1972
1972
1973
1973

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In extensive studies of PTH synthesis by human parathyroid cells (Martin et al, , 1972(Martin et al, , 1973 we have found no evidence for the existence in cells or in media of such low-molecular-weight peptides with PTH-like immunoreactivity. The peptides found in this cancer cell culture may represent synthesis of a number of incomplete PTH molecules by the cancer cells, or could result from a rapid and potent proteolytic process within the cells, leading to a rapid turnover of newly synthesized hormone and formation of fragments of the molecule.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In extensive studies of PTH synthesis by human parathyroid cells (Martin et al, , 1972(Martin et al, , 1973 we have found no evidence for the existence in cells or in media of such low-molecular-weight peptides with PTH-like immunoreactivity. The peptides found in this cancer cell culture may represent synthesis of a number of incomplete PTH molecules by the cancer cells, or could result from a rapid and potent proteolytic process within the cells, leading to a rapid turnover of newly synthesized hormone and formation of fragments of the molecule.…”
Section: Discussionmentioning
confidence: 73%
“…It seems unlikely that the fragments were generated by breakdown occurring in the medium, since conditioned medium (i.e. medium removed after prolonged incubation with cells) gave rise to no fragments of 1251-labelled PTH after incubation, and furthermore, in numerous experiments with human parathyroid cell cultures, this phenomenon of smaller-molecular-weight immunoreactive fragments has not been observed Martin, Greenberg & Melick, 1972). The radioactive secretions of the cells contained a small amount of PTH and a peptide of similar molecular weight to PTH (by its elution from Sephadex G-100), but more basic in charge, resembling in this respect proPTH, the recently discovered biosynthetic precursor of PTH (Hamilton, Macgregor, Chu & Cohn, 1971;Kemper, Habener, Potts & Rich, 1972).…”
Section: Discussionmentioning
confidence: 99%